Evaluation of serum interleukin-17 A and interleukin-22 levels in pediatric patients with autism spectrum disorder: a pilot study - Dina E. Sallam; Youstina S. Shaker; Gehan A. Mostafa; Reham M. El-Hossiny; Sara I. Taha; Mostafa Abd Elazeem Hassan Ahamed (BMC, 2024)
Abstract Background Many neurodevelopmental abnormalities are connected to autism spectrum disorder (ASD), which can result in inflammation and elevated cytokine levels due to immune system dysregulation. Interleukin (IL)-17 A and IL-22 have been linked to the regulation of host defense against pathogens at the barrier surface, the regeneration of injured tissue, and the integration of the neurological, endocrine, and immune systems. Several studies have investigated the possible connection between IL-17 A and ASD as well as the severity of behavioral symptoms, but few of them included IL-22. Objectives To measure serum levels of interleukin (IL)-17 A and IL-22 in children with ASD and to investigate their association with disease severity. Methods This pilot study was performed on 24 children with ASD and 24 matched controls. Childhood Autism Rating Scale (CARS) assessed ASD severity, and serum levels of IL-17 A and IL-22 were assessed by enzyme-linked immunosorbent assay (ELISA). Results In ASD patients, serum levels of IL-17 A and IL-22 showed a significant increase compared to controls (p-values < 0.001). We compared serum levels of IL-17 A and IL-22 according to the severity categories by CARS and could not find any significant differences (p-values > 0.05). Only IL-22 had a significant positive correlation with ASD severity by CARS scores. Conclusions Raised serum levels of IL-17 A and IL-22 are associated with ASD; only IL-22, not IL-17 A, is correlated with ASD severity. This finding proposes IL-22 as a possible future effective target for ASD treatment. To fully comprehend the significance of these cytokines in ASD and their possible effects on ASD diagnosis and treatment, more research on a wider scale is required.